Editing research : the author editing approach to providing effective support to writers of research papers - Matarese, Valerie (Information Today, Inc, 2016)
Valerie Matarese documents the history of author editing and illustrates, through interviews with experienced editors, the varied ways in which these language professionals support researchers in their efforts to publish.